Blogging for Creatives: How Designers, Artists, Crafters and Writers Can Blog to Make Contacts, Win Business and Build Success - Robin Houghton (Ilex, 2012)
"Blogging for Creatives" is the first approachable, non-techie guide to the blogosphere, complete with hundreds of tips, tricks and motivational stories from artistic bloggers who have started from scratch. It covers everything creatives need to know about how to design a beautiful, interesting blog that people will want to return to again and again such as how to design, publish and host a blog, as well as keeping it fresh, staying motivated and forging connections with others in the field. Professional advice is highly illustrated with examples of successful blogs, broken down into succinct types that work, helping the reader to identify and develop the style of blog they want.
Keywords: Blogging for Creatives: How Designers, Artists, Crafters and Writers Can Blog to Make Contacts, Win Business and Build Success; Blogging for Creatives: How Designers, Artists, Crafters and Writers Can Blog to Make Contacts, Win Business and Build Success